The Impact of Using Computer Games and Educational Programs on the Achievement and Growth of Creative Thinking among First-Grade Students in Arabic Language Course in Al-Karak - Fatima Khaled Al-Nawaisah (Britain International for Academic Research (BIAR) Publisher, 2022)
The study aimed to reveal the effect of using computer games and educational programs on the achievement and growth of creative thinking among first-grade students in the Arabic language course. The empirical approach was used; the study sample consisted of 59 students who were randomly assigned to three groups. To measure the effect of using computer games and educational programs on achievement, an achievement test was prepared in the Arabic language course by the researcher, and the Torrance Test of Creative Thinking was applied to determine the impact of using computer games and educational programs on the elements of creative thinking. The results did not show that there were statistically significant differences at 0.05  level in the achievement of the three groups, while the results resulted in the emergence of statistically significant differences at 0.05  level in the development of each creative thinking ability separately (fluency, flexibility, originality, and details), as well as in the development of The ability of creative thinking as a whole in favor of the first experimental group, which used educational computer games. In light of the results, the researcher makes a set of recommendations, including expanding the adoption of computer software and games for learning and teaching.